Hydrocarbon potential and depositional environments of Oligo-Miocene rocks in the Eastern Carpathians (Vrancea Nappe, Romania). (December 2015) - Sachsenhofer, R.F.; Hentschke, J.; Bechtel, A.; Coric, S.; Gratzer, R.; Gross, D.; Horsfield, B.; Rachetti, A.; Soliman, A.
Abstract: The Oligocene to early Miocene fine-grained succession in the Eastern Carpathians includes, from base to top the Lower Menilite (LMM), Bituminous Marl (BMM), Lower Dysodilic Shale (LDSM), and Upper Dysodilic Shale (UDSM) members. These stratigraphic units, constituting the main hydrocarbon source rocks in the Eastern Carpathians, have been studied in an outcrop section to determine its depositional environment and hydrocarbon potential. The LMM contains high amounts of TOC, but because of low thickness its source potential is limited. The organic matter of the overlying BMM is mainly derived from autochthonous marine organisms including bacterial biomass. TOC contents are moderate because of dilution by carbonate minerals. Calcareous nannoplankton dates the BMM into nannoplankton zones NP21-22. Salinity and redox conditions varied from reduced to slightly enhanced and from strictly anoxic to dysoxic. The LDSM contains carbonate-free black shale and sandstone beds deposited in a depositional lobe under anoxic conditions. Despite of high HI values, land plants form a significant part of the organic matter. Channel fill sediments form the top of the LDSM. The lower part of the early Miocene UDSM accumulated in a lobe, whereas its upper part represents a basin plain setting. MTTC ratios reflect a trend from slightly enhanced to slightly decreased normal marine salinity. The presence of aryl-isoprenoids suggests a temporary photic zone anoxia controlled by salinity variations. Both marine and terrestrial biomass contributed to the organic matter. A major change towards oxic conditions occurred at the boundary between the UDSM and the overlying Gura Soimului Formation. The studied succession can generate 6 t of hydrocarbons per square meter. All members are oil prone, but yield oil with different biomarker characteristics. This allows the identification of oil generated from different lithostratigraphic units. Highlights: Source potential of Oligo-Miocene rocks in E′ Carpathians has been investigated. Oligo-Miocene rocks are able to generate 6 tons of hydrocarbons per m 2 . Considerable vertical variations of source potential of Oligo-Miocene rocks exist. Links between depositional environment and source rock quality are highlighted. Parameters to distinguish oil from different Oligo-Miocene units are presented.